The Influence of Korean Wave K-Pop, Lifestyle, and Fanaticism on the Consumptive Behavior of K-Pop Fans on Students at the Bekasi Branch of Universitas Pelita Bangsa - Aidah, Siti; Supartono, Supartono (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was conducted at Universitas Pelita Bangsa, Bekasi City Branch, using a sample of 90 respondents from students at Universitas Pelita Bangsa, Bekasi City Branch. This research aims to partially determine the Korean Wave of K-Pop, Lifestyle, and Fanaticism of K-Pop Fans regarding consumer behavior. The method used in this research is quantitative. The results of this research show that the Korean Wave K-Pop partially has a significant effect on consumer behavior with a t-count value of 4.101 > t-table 1.662 and sig < 0.05. Lifestyle partially has a significant effect on consumer behavior with a t-count value of 2.558 > t-table 1.662 and sig 0.05. Fanaticism partially has a significant effect on consumer behavior with a t-count value of 5.182 > t-table 1.662 and sig < 0.05. The magnitude of the influence of the Korean Wave K-Pop, Lifestyle, and Fanaticism of K-Pop Fans on consumer behavior is 86.3%, then the remaining 13.7% is influenced by other independent factors and variables.